FORMATION OF RADIATION DEFECTS AND STRUCTURAL TRANSFORMATIONS IN QUARTZ CRYSTALS IRRADIATED WITH CHARGED PARTICLES (American Journal of Technology and Applied Sciences, 2026)
The paper investigates the gamma-luminescence (GL) spectra of iron-doped Fe quartz crystals irradiated with protons and deuterons. Within the temperature range of 77–155 K, the GL spectrum is characterized by a complex band in the 450–520 nm region. Using the Gaussian deconvolution method, the key components were identified at 470 nm (recombination at E'1-centers) and 490 nm (annihilation of self-trapped excitons). It is established that an increase in beam current density and the mass of incident particles (transition from protons to deuterons) leads to an increase in the intensity of the 470 nm band, which is explained by the enhanced efficiency of displacement and ionization-induced creation of oxygen vacancies. The anomalous intensity behavior in the 77–85 K range is interpreted as the thermal activation of charge carriers from shallow traps, while the sharp decline in emission at 155 K is attributed to thermal quenching according to the Mott-Seitz model. It is shown that the Fe impurity modifies the energy structure of radiation-induced defects and affects their thermal stability.